(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Disaster Assistance ProgramModels helps to identify the primary victims inseveral types of disaster and lists the disaster assistance program models thatcan be used in each case. Comparison of column 3 "Pre- Disaster AssistanceModels" and column 5 "Post-Disaster Assistance Models" showsthat both borrow heavily from normal development methodology. By understandingthese links, disaster managers will be more effective participants in bothdisaster and development activities. * This is normally an advantage because agencies working in developmentin a country can be effective where they have existing programs. Agenciesentering a country during the emergency have to learn their way around.